ANGIOSARCOMA OF THE LIVER - A CASE REPORT - Jayakumar, C.R.; Chua Kim Lian, Lilius (The ASEAN Journal of Radiology, 2023)
A 42 year old man presented to our hospital with right hypochondrial pain for 6 months. This had increased in severity and frequency over the last one week and was associated with fever, The patient was febrile and had slightly raised total white cell count. Ultrasonography revealed an enlarged liver with an inhomogeneous mass within the right lobe of the liver. In view of the clinical history, a provisional diagnosis of a liver asbcess was made. A percutaneous needle aspiration was performed under ultrasound guidance. There was no pus but blood stained fluid was aspirated instead. This was sent for cytology. Subsequently a CT scan of the abdomen was performed for further evaluation of the liver mass. This showed an ill-defined, predominantly hypodense mass in the right lobe of the liver and medial segment of the left lobe of the liver suggestive of a malignant liver tumour. A tru-cut biosy of the liver tumour was performed under CT guidance. The histopathological examination revealed that the liver tumour was hepatic angiosarcoma. The patient went on to develop brain metastasis. He was treated with radiotherapy but succumbed to the disease and died 3 months from the time of diagnosis. The significant aspects of hepatic angiosarcoma and the imaging modalities used are discussed.